Suspicious minds: An examination of trust-building in party mergers. (November 2019) - Keith, Dan; Sanderson-Nash, Emma; Wager, Alan
Here, we examine the understudied merger of the Social Democratic Party and the Liberal Party. This systematic study of the process which created the Liberal Democrats in 1988 adds to our understanding of what was a rare but important event in British politics. We demonstrate that it deviated from theoretical accounts of such mergers that stress the need for trust at the elite level. We recognise that inter-party trust can instead develop across the three faces of party organisation. We contribute a new typology for understanding these processes, and argue that existing studies are right to highlight that trust between the party in public office is important but wrong to conclude that its absence precludes mergers from occurring. Instead, we find that a lack of trust between parties in public office restricts the degree of delegation and increases the level of monitoring and formalisation, which can have damaging effects on the parties that emerge.